Patient Toward Physician Occupational Stigma Scale: Development of the Chinese Version - Fan Z; Chen H; Wu H; Zhang X (Psychology Research and Behavior Management, 2022)
Zhiguang Fan,1,2 Hongyan Chen,3 Hanwei Wu,4 Xinghai Zhang2 1Department of Education, Jilin International Studies University, Changchun City, Jilin Province, People’s Republic of China; 2Department of Marxism, Changchun University of Chinese Medicine, Changchun City, Jilin Province, People’s Republic of China; 3Department of Chinese Medicine, Changchun University of Chinese Medicine, Changchun City, Jilin Province, People’s Republic of China; 4Department of English, Jilin International Studies University, Changchun City, Jilin Province, People’s Republic of ChinaCorrespondence: Xinghai Zhang, Department of Marxism, Changchun University of Chinese Medicine, Boshuo Street 1035, Changchun City, Jilin Province, 130117, People’s Republic of China, Tel +86-431-84924101, Fax +86 1 594-831-4623, Email zhangxh01@ccucm.edu.cnBackground/Objective: Physicians’ occupational stigma could eradicate physician-patient trust, threatening physicians’ social status and occupational reputation. Hitherto, there has been no scale obtaining good psychometric properties to assess patients’ stigma toward physicians. The present study aimed to develop the Patient toward Physician Occupational Stigma Scale (PPOSS) and examine its reliability and validity.Methods: The questionnaire comprising sociodemographic information and the PPOSS were employed to survey 645 Chinese patients in two phases. In Sample 2, the Wake Forest Physician Trust Scale (WFOTS), the Intolerance of Uncertainty Scale-12 (IUS-12), and the Brief Illness Perception Questionnaire (BIPQ) were tested.Results: The PPOSS includes 19 items subsumed into three dimensions of stereotype, discrimination, and prejudice. According to the results of confirmatory factor analysis (CFA), the three-factor model fitted well (χ2/df=2.065, RMSEA=0.057, SRMR=0.045, RFI=0.904, CFI=0.956, IFI=0.956, PNFI=0.779, PCFI=0.811). The PPOSS was significantly negatively correlated with the WFOTS, and significantly positively correlated with the IUS-12 and the BIPQ. The Cronbach’s alpha coefficients for the total scale and each dimension were between 0.87 and 0.94, and the split-half reliability coefficients were between 0.84 and 0.93. Besides, the PPOSS had the measurement invariance across gender.Conclusion: With its satisfactory psychometric properties, the PPOSS can be used as an effective instrument to assess patients’ stigma toward physicians.Keywords: physicians, occupational stigma, reliability, validity